Impact of high sodium intake on stomach cancer burden in China: A comprehensive analysis from 1990 to 2021 - Zhouwei Zhan; Yi Zeng; Rui Huang; Jiami Yu; Hui Lin; Xiaojie Wang; Zengqing Guo; Bijuan Chen (PLoS ONE, 2026)
Background Stomach cancer remains a significant public health concern in China, with dietary factors, particularly high sodium intake, being major contributors. This study aimed to quantify the trends, demographic disparities, and contributing factors to this burden from 1990 to 2021. Methods Data from the Global Burden of Disease Study (GBD) 2021 were used to assess the burden of stomach cancer attributable to high sodium intake. The study included age-standardized mortality rates (ASMR), disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs). Joinpoint regression and age-period-cohort (APC) analysis were performed to identify significant trends and changes. Decomposition analysis was used to identify the impacts of aging, epidemiological changes, and population growth. Results In 2021, stomach cancer attributable to high sodium intake resulted in 36,958 deaths in China, with males (26,171) being more affected than females (10,786). The ASMR was significantly higher in males (2.71 per 100,000) than in females (0.99 per 100,000). DALYs totaled 883,435, with males contributing 643,008 and females 240,427. Age-standardized DALY rates were 62.16 for males and 22.15 for females. The age-standardized rates for YLDs and YLLs were also higher in males than females. Although ASMR and age-standardized DALYs rates declined overall (AAPC: −2.45% and −2.76%, respectively), absolute burden increased due to aging and population growth. Compared to global averages, China’s age-standardized rates remained higher, despite notable improvements since 1990. APC analysis showed elevated risks in older age groups, declining period effects, and lower burden among recent birth cohorts. Decomposition analysis indicated that aging and population growth contributed to increased deaths, while epidemiological changes led to a reduction. Conclusions Despite declining age-standardized rates, the absolute burden of stomach cancer linked to high sodium remains substantial in China. Males and older adults are disproportionately affected. Population aging and growth are key contributors, while public health interventions have mitigated the burden to some extent. Sustained, gender-sensitive strategies focused on sodium reduction are essential to further lower disease impact.